2003
DOI: 10.1248/cpb.51.187
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Chemical Constituents of Stem Bark of Millettia leucantha: Isolation of New Chalcones with Cytotoxic, Anti-herpes Simplex Virus and Anti-inflammatory Activities.

Abstract: The genus Millettia WEIGHT et ARN. (Leguminosae) consists of ca. 100 old world species of climbers and trees, and their seeds and other parts are in some cases known to show insecticidal and piscicidal properties.1) In previous studies 2) flavonoids, isoflavonoids and alkaloids were isolated as chemical components. M. leucantha KURZ is a lofty tree, with pinnate leaves and white flowers, growing throughout Thailand 3); however, its medicinal use is unknown. The present investigation deals with the isolation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…This class of flavonoids is quite rare in the plant kingdom. Interestingly, dihydrochalcones have previously been identified in a few Fabaceae species, but no nod-inducing activity has been reported for those compounds, whereas several chalcones are known to be nod inducers (2,41,50,54).…”
Section: Discussionmentioning
confidence: 99%
“…This class of flavonoids is quite rare in the plant kingdom. Interestingly, dihydrochalcones have previously been identified in a few Fabaceae species, but no nod-inducing activity has been reported for those compounds, whereas several chalcones are known to be nod inducers (2,41,50,54).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their structural simplicity, these compounds exhibit diverse important pharmacological effects on biological systems including anti-inflammatory (Correa et al, 2001), anti-mycobacterial (Rojas et al, 2002), antimalarial (Chen et al, 1994), anti-fungal (Boeck et al, 2006;Lopez et al, 2001), anti-viral (Phrutivorapongkul et al, 2003), and anti-nociceptive (Correa et al, 2001). Previous studies have shown that chalcones bearing phenyl group with chloro and hydroxyl substituents inhibit nitric oxide (NO) synthesis as well as inducible nitric oxide synthase (iNOS) protein expression in RAW 264.7 cells (Ko et al, 2003;Won et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that M. brandisiana is the first Thai Millettia species to produce isoflavones and rotenoids; other species of Millettia in Thailand have yielded only flavones and chalcones. 2,22) In addition, 12a-hydroxy-a-toxicarol (11) seems worthy of additional testing further to evaluate its potential as an anti-inflammatory agent.…”
Section: Resultsmentioning
confidence: 99%